The anniversary : a novel - Bishop, Stephanie, 1979- (Black Cat, 2023)
"Ascendant novelist J.B. Blackwood is on a cruise with her husband, Patrick, to celebrate their wedding anniversary. Patrick is older than J.B., formerly her professor, now a film director and cult figure. But now his success is starting to wane and J.B. is on the cusp of winning a major literary prize. Her art has been forever overseen by him; now it may overshadow his. For days they sail in the sun, nothing but dark water all around them. Then a storm hits and Patrick falls from the ship. J.B. is left alone as the search for what happened to Patrick--and the truth about their marriage--begins."--